Hospital Stay in Nosocomial Infections - Herry Garna (Indonesian Pediatric Society, 1993)
A 9 month prospective study on nosocomial infections was held from August 1988 till April 1989 at the Department of Child Health, Medical School, Padjadjaran University, Hasan Sadikin Hospital Bandung. The purpose of the study was to compare the duration of hospitalization in patients with and without nosocomial infections. The Department of Child Health has 4 main wards, A2 (for low sosioeconomic families), A3 (for middle and high socioeconomic families), R-17 (for neonates) anda NICU. There were 4328 hospitalized pediatrica patients observed consisting of 293 children (29 9%) in A2, 485 (11.2%) in A3, 2487 (57.5%) in R-17, and 41 episodes in NICU, showing rates of 9.9% in A2, 4.5% in A3, 8.8% in R-17 and 65.1% in NICU. The means hospital stay of patients with nosocomial infecitons were 26.77 and 22.44 days in A2 and NICU, while in A3 and R-17 17.61 and 6.75 days. The means hospital stay of patients without nosocomial infecitons were 13.11 and 9.24 days in A2 and NICU, and 1 0.48 and 3.10 days In A3 and R-1 7. Length of stay specific nosocomial infeciton rate rose with the duration of hospitalization, with 3 2% of patients staying upt to 6 days, 16.7% of patients staying 7-13 days, 19.7% of patients staying 14 to 20 days, and 48,8% of patients staying 35 days or more. It can be concluded that the longer the length of stay, the higher the number of nosocomial infections. The overall mean hospital stay of patients with nosocomial infection was 2.4 times higher than that without nosocomial infection.